Pengaruh Pajak, Intangible Assets, Dan Ukuran Perusahaan Terhadap Transfer Pricing - Astri Wulandari; Dini Fitrianti (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to analyze how tax variables, intangible assets and company size affect transfer pricing in Energy sector companies listed on the Indonesian stock exchange. The research method used is quantitative research method with secondary data obtained indirectly by collecting financial reports and annual reports from Energy companies in 2018-2022 published on the IDX website or the official website of each company. In this study, to obtain a sample, special criteria are needed, so the purposive sampling method is used. This study has a population of 84 companies and obtained 11 company samples and the observation results include 55 financial statement data for five years in the period 2018-2022. The test analysis used in this study is using EViews 13 software. This study obtained the results, namely partially, taxes have no effect on transfer pricing, intangible assets affect transfer pricing, company size affects transfer pricing, and simultaneously taxes, intangible assets, and company size affect transfer pricing.